2020
DOI: 10.1364/josab.376267
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of quantum key distribution in underwater turbulence channels

Abstract: The current literature on quantum key distribution (QKD) is mainly limited to the transmissions over fiber optic, atmospheric or satellite links and are not directly applicable to underwater environments with different channel characteristics. In this paper, we analyze the quantum bit error rate (QBER) and secret key rate (SKR) performance of the well-known BB84 protocol in underwater channels. As path loss model, we consider a modified version of Beer-Lambert formula which takes into account the effect of sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…Tis section will now provide closed-form bounds for these parameters when applying the BB84 protocol in free-space underwater channels. We consider the impact of difraction, turbulence, path loss, and other important factors, as reported in studies [81,82]. We 10…”
Section: The Underwater Quantum Channelmentioning
confidence: 99%
See 4 more Smart Citations
“…Tis section will now provide closed-form bounds for these parameters when applying the BB84 protocol in free-space underwater channels. We consider the impact of difraction, turbulence, path loss, and other important factors, as reported in studies [81,82]. We 10…”
Section: The Underwater Quantum Channelmentioning
confidence: 99%
“…By inserting ( 16) into (13), one can easily see that the transmission of the i-th input mode (i.e., �� � P T 􏽰 u 0 (r) � �� � P T 􏽰 f i (r)) originates the feld pattern u(ρ) � �������� A(L)μ i P T 􏽰 ϕ i (ρ) at P 1 , and the resulting fraction of captured photons (15) is c � A(L) • μ i . As shown in [77,81], to fnd a practical lower bound on the underwater quantum channel QBER, we can limit our eforts to evaluating a lower bound on the expected value of the maximum modal transmittivity μ 1 , i.e., a value μ turb such that E[μ 1 ] ≥ μ turb [81]. It can be shown that…”
Section: ���� � A(l)mentioning
confidence: 99%
See 3 more Smart Citations